Environmental sustainability issues in Malaysian metal and fabrication SMEs: comparative analysis from a case study perspectives - Abdullah Sidek, 'Atiah; Backhouse, Chris (2014)
Environmental issues are now becoming a constant if not a dominant issues in society and government agenda. There is an expectation that all institutions especially industries take proactive steps towards improving their environmental performance. Malaysia recognises this shift and has move towards a more positive approach in promoting environmentally sound and sustainable development practices for industries and businesses including SMEs. Yet there are many aspects of the SMEs sector are still isolated and need to be investigated. This case study is the first part of the investigation and perceived as an opportunity to explore and understand the weakness of the current system in Malaysia. A series of interviews were carried out with senior management of metal and fabrication SMEs in United Kingdom and Malaysia to understand the attitude towards environmental sustainability, current environmental and operation performances, and other key improvement areas. This paper presented the findings of the case study and the comparative analysis helps identify key areas for continuous improvement, in order to better promote environmental sustainability to Malaysian SMEs especially in the metal and fabrication sector